The Accountability Concept and Accounting - a Theoretical Approach - Zyznarska-Dworczak, Beata (Studia Oeconomica Posnaniensia, 2019)
The aim of the study is to assess the impact of a concept of accountability on accounting and the role of accounting in the implementation of accountability concepts in an enterprise. An analysis of the significance of the accountability concept was conducted, indicating in particular the types of this concept and the areas of its implementation in a company. Against this background, based on deductive reasoning, the thesis of the article has been proved. The paper shows that the accountability concept directs the development of accounting to support the settlement of corporate responsibility, in its reporting, management and control dimension. The paper shows that a cascade of accountability within an enterprise determines the areas in which accounting is important.